Which helps me better? Students’ reasons of using online grammar-checking tools in academic writing - Alfianofita, Anindya (Erudita: Journal of English Language Teaching, 2025)
Recent studies have mainly focused on the student’s perceptions and the effectiveness of online grammar-checking tools during the academic writing process. The concerns related to the kind of online grammar checkers and reasons for using the tools also need to be taken into attention. This present research aims to answer the research questions which are (1) What online grammar-checking tools do students use to correct grammar in academic writing, and (2) What are the reasons behind students’ use of online grammar-checking tools in academic writing.  Data were collected by face-to-face interviewing 9 students who were purposefully selected using online grammar checkers during their article writing process. The research findings revealed that (1) Online grammar checkers used by students to correct grammar in academic writing are Grammarly, QuillBot, Sider AI, and Google Docs Automatic Correction, (2) There are four reasons behind students’ use of online grammar checkers in academic writing; offering convenience and time-saving, improving accuracy and readability, helping students in the process of editing & revising the draft, and to learn and improve grammar skills. It is recommended, however, that students should manually review and correct for missed grammatical errors considering that online grammar checkers are not perfect.